Synthesis and characterization of biochars modified with natural deep eutectic solvent (NADES) for dipyrone removal from aqueous medium - G.S. Guimarães, Taciana; Barros, Lucélia A.; Silva, Ricardo Santos; Gonzalez, Mario H. [UNESP]; Carrilho, Elma N.V.M.; Labuto, Geórgia (Elsevier, 2023)
Dipyrone is a widely commercialized substance that has been linked to DNA damage in aquatic organisms. As with other pharmaceutical compounds found in water bodies, it is a global concern that affects water security. Adsorption is considered a viable alternative for removing pharmaceuticals from water, particularly when the adsorbents are derived from renewable sources like agro-industrial wastes. In this study, biochars were prepared from yeast waste (YWB), cork powder (CPB) and old coffee grounds (CGB), and were functionalized with a natural deep eutectic solvent (NADES) based on citric acid and sucrose, resulting in YWB-NADES, CPB-NADES, and CGB-NADES. The adsorbents were characterized and used to dipyrone removal from aqueous medium. The dipyrone removal by CGB-NADES at pH 6 reached 21.92 ± 0.5 mg/L (89.12% ± 1.3) and 16.97 ± 0.8 mg/L (68.96% ± 1.9) for deionized and freshwater from a reservoir, respectively. The kinetics adsorption was described by the pseudo-second order, and different isotherm model best fit the experimental data, suggesting that both chemisorption and physisorption mechanisms govern the adsorption of dipyrone by the biochars functionalized with NADES. The synthesis of the functionalized biochars scored 96 points in the Eco Scale, indicating that these adsorbents are environmentally friendly and, in conjunction with their high adsorption capacity, are viable for dipyrone removal in water and effluent treatment.
Keywords: Cork powder; Functionalized biochars; Green solvent; Old coffee ground; Water treatment; Yeast waste